Environmental Sustainability and The Demand For Recycled Paper: A Case Study of Production and Supply Chain Management at PT. Recycled Paper Hub in the B2B Industry - Fachmi Firzandi Prima; Rhian Indradewa; Tantri Yanuar Rahmat Syah; Unggul Kustiawan (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
This paper aims to explore PT. Recycled Paper Hub's response to the increasing demand for recycled paper within the context of sustainable production management and supply chain management, with a focus on the B2B industry. The study encompasses an analysis of the company's practices in managing relationships with suppliers of recycled paper, enhancing operational efficiency, and mitigating environmental impacts from its operations. PT. Recycled Paper Hub, a B2B company specializing in processing recycled paper into bales, faces rising demand for its products. This article presents research findings on how the company addresses the growing market demand through the utilization of advanced production technology and the application of lean manufacturing methods to minimize waste. Furthermore, the research evaluates how PT. Recycled Paper Hub manages relationships with suppliers of recycled paper to ensure stable and high-quality supply. Strategic partnerships with suppliers of recycled paper are identified as key success factors in meeting increasing demand. The research findings indicate that the increased demand for bales of recycled paper not only reduces waste and emissions but also reinforces PT. Recycled Paper Hub's commitment to sustainability. These findings offer valuable insights for the paper industry and other companies seeking to adopt more sustainable business models.